Exploring the practical knowledge of eccentric resistance training in high-performance strength and conditioning practitioners. Issue 1 (February 2020) - Harden, Mellissa; Bruce, Claire; Wolf, Alex; Hicks, Kirsty M; Howatson, Glyn
Habitual use of eccentric exercise has been recognised to increase strength and power; however, the current body of knowledge has limited potential to understand the application of such resistance training in athletic populations. In order to develop appropriate applied research, that relates to elite athletic populations, it is vital to appreciate the practical knowledge of strength and conditioning practitioners operating in high-performance environments. This study summarised the questionnaire responses from 100 strength and conditioning practitioners operating in performance sport relating to questions such as the training effects to various eccentric resistance training regimes, the rationale for the use of these techniques and the knowledge supporting its application. The combination of closed and open-ended questions enabled a thematic analysis to be conducted. There was evidence that practitioners employed a variety of eccentric training methodologies; however, there was interest in gaining greater understanding of the training dose to bring about the optimal adaptive changes, and importantly how this might translate to sport-specific performance. In addition, practitioners would welcome recommendations associated with eccentric training, whilst concurrently minimising the issues of excessive fatigue, muscle damage and soreness. The training effects of interest included neural, architectural and morphological adaptations and, importantly, translation to performance of sports-specific skills. Collectively, these responses called for more practically relevant research to be conducted within the high-performance environment, alongside more opportunities for professional development through learning and knowledge-sharing opportunities. The outcomes summarised in this work should inform future applied research projects and educational content relating to eccentric training.